2014
DOI: 10.2337/db14-0061
|View full text |Cite
|
Sign up to set email alerts
|

GATA4 Mutations Are a Cause of Neonatal and Childhood-Onset Diabetes

Abstract: The GATA family zinc finger transcription factors GATA4 and GATA6 are known to play important roles in the development of the pancreas. In mice, both Gata4 and Gata6 are required for pancreatic development. In humans, GATA6 haploinsufficiency can cause pancreatic agenesis and heart defects. Congenital heart defects also are common in patients with GATA4 mutations and deletions, but the role of GATA4 in the developing human pancreas is unproven. We report five patients with deletions (n = 4) or mutations of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(73 citation statements)
references
References 24 publications
(29 reference statements)
2
70
0
1
Order By: Relevance
“…); the later expression of GATA 4 could contribute to the less severe phenotype of individuals carrying GATA4 vs GATA6 mutations [29,30].…”
Section: Resultsmentioning
confidence: 99%
“…); the later expression of GATA 4 could contribute to the less severe phenotype of individuals carrying GATA4 vs GATA6 mutations [29,30].…”
Section: Resultsmentioning
confidence: 99%
“…The ventral and dorsal pancreatic buds at CS13 are marked by the transcription factors SRY (sex-determining region Y)-box 9 (SOX9), PDX1 and GATA binding protein 4 (GATA4) (Piper et al, 2004;Jennings et al, 2013), all of which are required for (Stoffers et al, 1997;Piper et al, 2002;Shaw-Smith et al, 2014). The dorsal bud at CS13 is also characterized by the appearance of microlumens (Jennings et al, 2013): the first sign of a developing luminal network by which acinar secretions will eventually drain into the intestine (Kesavan et al, 2009;Villasenor et al, 2010).…”
Section: Timeline and Regulators Of Human Pancreas Development Pancrementioning
confidence: 99%
“…Using a Cre-lox approach, we previously demonstrated that simultaneous deletion of Gata4 and Gata6 from pancreatic progenitor cells leads to pancreatic agenesis in newborn mice (Carrasco et al, 2012;Xuan et al, 2012). The importance of GATA4 and GATA6 in human pancreas development has also been highlighted in reports of genetic cases of human pancreatic agenesis: GATA6 haploinsufficiency contributes to the majority of pancreatic agenesis cases (Lango Allen et al, 2012), and GATA4 haploinsufficiency has been documented in a small number of patients with pancreatic agenesis (Shaw-Smith et al, 2014).…”
Section: Introductionmentioning
confidence: 99%